Building Empowered Online Communities: A Case Study on Brand Community in social media - Mandung, Fitriani; Mangkona, Suriyanti; Putra, Aditya Halim Perdana Kusuma (International Journal of Artificial Intelligence Research, 2023)
The digital revolution has reshaped the dynamics of consumer-brand interactions, placing online brand communities at the forefront of engagement strategies. This comprehensive discourse synthesizes discussions surrounding a collection of research papers that illuminate the nuanced dimensions of these digital communities. Delving into diverse themes, from empowerment and gamification to values alignment and cross-cultural dynamics, this exploration unravels the intricate fabric of online brand communities. Through a meticulous analysis of these papers, the abstract underlines the resonance of themes across studies, offering insights into the manifold ways brands and consumers interact in the digital ecosystem. Moreover, it highlights the practical implications these insights bear for managerial practices and steering strategies that harness the potential of online brand communities. Additionally, these abstracts underscore the contributions made to theoretical foundations, enriching our understanding of contemporary consumer-brand relationships.